Graphene Quantum Dots-Supported Palladium Nanoparticles for Efficient Electrocatalytic Reduction of Oxygen in Alkaline Media - Deming, Christopher P; Mercado, Rene; Gadiraju, Vamsi; Sweeney, Samantha W; Khan, Mohammad; Chen, Shaowei (ACS sustainable chemistry & engineering, 2015)
Graphene quantum dots (GQDs)-supported palladium nanoparticles were synthesized by thermolytic reduction of PdCl2 in 1,2-propanediol at 80 °C in the presence of GQDs and then were subject to hydrothermal treatment at an elevated temperature within the range of 140 to 200 °C. Transmission electron microscopic measurements showed a raspberry-like morphology for the samples before and after hydrothermal treatment at temperatures ≤160 °C, where nanoparticles of ca. 8 nm in diameter formed large aggregates in the range of 50 to 100 nm in diameter, and at higher hydrothermal temperatures (180 and 200 °C), chain-like nanostructures were formed instead. X-ray photoelectron and Raman spectroscopic measurements revealed that the GQD structural defects were readily removed by hydrothermal treatments, and the defect concentrations exhibited a clear diminishment with increasing hydrothermal temperature, as indicated by the loss of oxygenated carbons in XPS and a drop in the D to G band ratio in Raman measurements. Voltammetric studies showed apparent electrocatalytic activity toward oxygen reduction, with a volcano-shaped variation of the activity with GQD defect concentration, and the peak activity was observed for the sample prepared at 180 °C with a mass activity of 23.9 A/gPd and specific activity of 1.08 A/m2 at +0.9 V vs RHE. This peak activity is attributed to optimal interactions between Pd and GQD where the GQD defects promoted charge transfer from metal to GQDs and hence weakened interactions with oxygenated intermediates, leading to enhanced ORR activity. The corresponding defect concentration was higher than that identified with the platinum counterparts due to the stronger affinity of oxygen to palladium.